Study on Influence Factors of Carbon Emission in Hubei's Logistics Industry Based on LMDI Method - Qin, XU (2021 6th International Conference on Transportation Information and Safety (ICTIS), 2021)
China's total carbon emissions have surpassed those of the United States and the European Union, and becomes the largest carbon emitter in the world. As the vanguard of the national economy, the logistics and transportation industry is closely related to energy consumption and carbon emission. Based on this, this paper takes the logistics industry as the research subject,and takes the energy consumption of the logistics transportation industry in Hubei Province as the basic data, Using the LMDI decomposition method, first this paper analyzes the present situation and the trend change of the carbon emission of the logistics transportation industry in Hubei Province, then the paper analyzes the driving factors that affect the change of carbon emission intensity of logistics industry in Hubei Province, and finally puts forward some suggestions and measures on the low-carbon path of logistics industry in Hubei Province, which can provide effective support for the development of low-carbon industry in Hubei Province